Indigenous Identity Development through Sport - McCourt, James (2021)
Physical activity, games, sport and youth have a rich history within Indigenous communities, but that is not reflected in academic literature. For years, scholars wrote about Indigenous communities and people and not with them. Aspects of everyday life, such as physical activity, games and sport were seen as trivial and often marginalized. By listening to the narratives of Indigenous youth we get an understanding of the complexities of their lives. Research for, by and with Indigenous communities is growing. This thesis examines the idea of Indigenous identity navigation through sport by using an Indigenous research methodology, the strengths approach, the framework of two-eyed seeing and a community based participatory research strategy. The method for collecting data was through individual interviews and a traditional Indigenous talking circle. The research question and interview questions were developed with the community-based research assistant. Participants/Coresearchers took part in individual interviews that examined the impact that the Anishinabe Pride basketball program has had on their lives. The use of a talking circle was instrumental in providing a space for Indigenous voices to be heard and in confirming understanding gained through individual interviews. A separate discussion was held with Jackie Anderson, the creator of the Anishinabe Pride program, after the analysis of data to confirm results. Three themes emerged through data analysis: education, culture and community. While each theme is distinctly different, each also interconnects within the Anishinabe Pride program. Through the use of oral narrative, co-researchers shared stories and experiences of the Anishinabe Pride program and the impact it has had on their lives. It is these narratives that help define what Indigenous identity navigation looks like through the lens of the Anishinabe Pride basketball program. M.Ed.